Towards a Regional Strategy to Strengthen the Nurse Workforce of the English-speaking CARICOM : International Legal Instruments, Agreements and Obligations - World Bank (World Bank, 2012)
The supply of nurses in the English-Speaking Caribbean is insufficient to meet the demand with growing shortages fuelled by the health needs of a rapidly aging population and tremendous losses of human capital occurring at multiple points in the markets. In defining the scope of commitments of a regional legal agreement, English-Speaking Caribbean Community (ES CARICOM) states will have to ascertain whether states would commit to actions to strengthen the nurse workforce or the health workforce more broadly. While the challenges of strengthening the nurse workforce have been systematically assessed, information about other groups of health professionals remains patchy. In 2008, at the request of the Ministers of Health, the World Bank initiated a stream of work to strengthen the nurse workforce in the English-speaking Caribbean. The study estimated the stock of nurses in the ES CARICOM at approximately 7,800 in 2007 with growing shortages under existing policies at 3,400 in 2007 increasing to 10,700 nurses in 2025 due to the health needs of a rapidly aging population. There are two types of international legal instruments: legally binding instruments or treaties; and non-legally binding instruments.